Mamdani Fuzzy Implementation for New Student Admission Selection - Felix Andika Dwiyanto; Mohammad Rizky Kurniawan; Syaichul Fitrian Akbar; Anik Nur Handayani (Jurnal Informatika, 2019)
In the selection process for New Student Admissions, there are many prospective new students. However, not all candidates accepted at a school. They must be passing through the selection stage by following specific criteria. Therefore, schools need to select candidates following specific criteria to make the best selection of students. Especially in vocational high school (VHS), the selection processes are more complex. It is because every department in VHS certainly has its criteria (different in each department). Based on the background, this study aims to propose a method based on Mamdani Fuzzy that can be applied to the new student admission selection process. There are three main stages in this method, which are fuzzification, inference, and defuzzification.